Flebotomíneos (Diptera: Psychodidae) en la Reserva Natural del Cañón del Río Claro (Antioquia), Colombia (2010)
ABSTRACT: Considering the endemicity of leishmaniasis in the Antioquia region, Colombia, it is important to have an updated distribution of different phlebotomine sand y species, as their distribution is a relevant factor for establishing the role of such species in the disease epidemiology. This study evaluated the current composition of phlebotomine sand ies of the genera Lutzomyia and Brumptomyia in the natural reserve of the Río Claro Canyon (Antioquia), following entomological surveys in May, June, and August of 2008. Insects were collected using light traps such as CDC and Shannon, and through active searches using mouth aspirators as collecting devices on substrates such as tree holes and buttresses. We provide the rst record of Lutzomyia ayrozai, L. camposi, L. carrerai thula, L. dasymera, L. isovespertilionis, L. micropyga, L. olmeca bicolor, L. cayennensis cayennensis, L. pilosa, and L. shannoni in the reserve of Río Claro. We also report the rst nding of Brumptomyia hamata and B. mesai in the Antioquia region, highlighting the occurrence of L. gomezi, L. hartmanni, L. panamensis, L. trapidoi, and L. yuilli because these species are known as potential vectors of cutaneous leishmaniasis in Colombia. Documenting the presence of L. longipalpis (Lutz and Neiva) ten years after its previous record in the area is noteworthy, given that this species is the vector of Leishmania infantum, the aetiological agent of visceral leishmaniasis.